Is the response of insectivorous bats to vegetation cover scale – dependent? - Rodrigues, Camila Moniz Freire (2019)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Ciências Biológicas, Departamento de Ecologia, 2019.